2002
DOI: 10.1523/jneurosci.22-24-10699.2002
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Biochemical Analysis of a Sodium Channel β1 Subunit Mutation Responsible for Generalized Epilepsy with Febrile Seizures Plus Type 1

Abstract: Generalized epilepsy with febrile seizures plus type 1 is an inherited human epileptic syndrome, associated with a cysteine-to-tryptophan (C121W) mutation in the extracellular immunoglobin domain of the auxiliary beta1 subunit of the voltage-gated sodium channel. The mutation disrupts beta1 function, but how this leads to epilepsy is not understood. In this study, we make several observations that may be relevant for understanding why this beta1 mutation results in seizures. First, using electrophysiological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
131
3
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 53 publications
11
131
3
5
Order By: Relevance
“…Scn1b (β1) null mice are ataxic, experience spontaneous seizures, and exhibit a prolonged cardiac QT interval, demonstrating that β1 modulates electrical excitability in vivo (12,13). Consistent with this, human mutations in SCN1B result in epilepsy and arrhythmia (14)(15)(16)(17)(18)(19)(20)(21). As a member of the Ig superfamily of cell adhesion molecules (CAMs), β1 mediates cellular aggregation, cytoskeletal recruitment, and extracellular matrix interactions in vitro (11).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Scn1b (β1) null mice are ataxic, experience spontaneous seizures, and exhibit a prolonged cardiac QT interval, demonstrating that β1 modulates electrical excitability in vivo (12,13). Consistent with this, human mutations in SCN1B result in epilepsy and arrhythmia (14)(15)(16)(17)(18)(19)(20)(21). As a member of the Ig superfamily of cell adhesion molecules (CAMs), β1 mediates cellular aggregation, cytoskeletal recruitment, and extracellular matrix interactions in vitro (11).…”
mentioning
confidence: 71%
“…Given that Scn1b mutations result in channelopathies in vivo (12)(13)(14)(15)(16)(17)(18)(19)(20)(21), and that β1-mediated neurite outgrowth in CGNs requires I Na and Na v 1.6, we postulated that β1 might regulate electrical excitability in the cerebellum. To test this, we recorded APs in P12-13 WT and Scn1b null CGNs in cerebellar slices by whole-cell patch clamping.…”
Section: Resultsmentioning
confidence: 99%
“…Although the observed seizure activity may be caused by altered sodium channel isoform expression in the hippocampus, our present results suggest that errors in neurite extension and pathfinding may also contribute. A human mutation in SCN1B that causes generalized epilepsy with febrile seizures plus type 1 results in the replacement of a key cysteine residue in the ␤1 Ig loop domain with tryptophan (36,37). We have shown that, in addition to inhibiting ␤1-mediated channel modulation, this mutation abolishes ␤1-mediated homophilic cell adhesive interactions (37).…”
Section: Discussionmentioning
confidence: 92%
“…Lymphocyte T-killer CD8 receptor, which we used as negative control, has a similar structure (Cole and Gao, 2004). The GEFSϩ C121W mutation of ␤1, which we used in some of the experiments, destroys the intramolecular disulfide bridge and inhibits ␤1 function (Wallace et al, 1998;Meadows et al, 2002) and is depicted as a hollow circle. ␤2 and ␤4 subunits are covalently linked to the ␣ subunit by disulfide bridges (dashed-dotted line), but the cysteine residues implicated have not been identified yet.…”
Section: Methodsmentioning
confidence: 99%
“…1 and Fig. 5C) destroys a disulfide bridge in the extracellular Ig-loop, and the mutant is a loss of function, the capacity of which to modulate ␣ subunit functions and to establish extracellular protein-protein interactions is impaired (Wallace et al, 1998;Meadows et al, 2002). Coexpression of hNa v 1.1-M1841T and ␤1C121W mutants induced a 2.6-fold increase in current density (Fig.…”
Section: All the Accessory Subunits Can Rescue Hna V 11-m1841tmentioning
confidence: 97%